Avaliação dos sintomas neuropsiquiátricos na doença de Alzheimer - Carrasco, Kátia Giugioli (2013)
Psychiatric disorders have been the major institutionalization cause for demented patients. Objective: Assess the neuropsychiatric symptoms over the several phases of the Alzheimer Disease. Method: The research was carried out in the Neurogeriatric Outpatient Clinic of the School Hospital. 89 patients were evaluated with a diagnosis of probable Alzheimer Disease. For data collection were used Mini Mental State Exam (MMSE), Neuropsychological Assessment, Blessed Rating for Dementia, Clinical Dementia Rating, Depression DSM4 Criteria, Geriatric Depression Scale, Neuropsychiatric Inventory. Results: The results evidenced the distribution of neuropsychiatric symptoms during the evolution such as: apathy in 66% (n = 59); agitation in 63% (n = 56), depression and irritability in 48% (n = 43), respectively, anxiety in 47% (n = 42), disinhibition in 36% (n = 32), delirium in 34% (n = 30), nocturnal behavior (NB) in 31% (n = 28) and aberrant motor behavior (AMB) in 27% (n = 24), appetite alterations in 26% (n = 23), hallucinations 17% (n = 15) and euphoria in 3% (n = 3). Conclusions: The neuropsychiatric symptoms most commonly found in this study were apathy, agitation, depression and irritability, and the least found were loss of appetite, hallucinations and euphoria.